The study of corporate risk disclosure in the case of Thai listed companies - Kongprajya, Chalida (2010)
In this age of globalization, firms are automatically put into a more vulnerable position to risks. This affects both business operation of the firms and decision making process of stakeholders. Therefore, risk management and risk reporting is gaining more interest from business, as well as academic community.